The Thieves Strategy in Teaching Reading Comprehension of Descriptive Text at MTs Fatahillah Tarempa - wanto, joko is (English Language Education, Universitas Internasional Batam, 2021)
In teaching and learning English, many students have difficulty understanding the text in a reading, especially the descriptive text. Therefore, the objective of this research was to find out the effectiveness of the THIEVES strategy in teaching reading comprehension of descriptive text at the eighth-grade students of Madrasah Tsanawiyah Fatahillah Tarempa. It was an experimental research using one group pretest-posttest design. The total population is 109 students of Madrasah Tsanawiyah Fatahillah Tarempa. In this research, the researcher used purposive sampling with a sample of 35 eighth-grade students of Madrasah Tsanawiyah Fatahillah Tarempa. To collect the data, the researcher used tests and questionnaires. The test consists of a pre-test and post-test to determine how effective is the THIEVES strategy in reading comprehension of descriptive text. And using a questionnaire to know the students respond to the THIEVES strategy. In this research, the mean score of the pre-test was 63,86 before the treatment. After the treatment, the mean score of the post-test was 79.43. Then the researcher used the t table to calculate and hypothesize. The result showed that the test of (t-table = df = 0.6817 = 34) at the 5% significance level. The questionnaire showed that students' responses to the THIEVES strategy in reading comprehension of descriptive texts are ACCEPTABLE. Based on the results, it can be concluded that the THIEVES strategy was effective in teaching reading comprehension of descriptive text at the eighth-grade students of Madrasah Tsanawiyah Fatahillah Tarempa.